Strategi Humas dalam Membangun Citra Pemerintah DKI Jakarta (Bansos Sembako di Kecamatan Sawah Besar, Jakarta Pusat) - Ariel Hizkia; Agustrijanto (UNIVERSITAS KALBIS, 2022)
Public relations has different strategies in shaping the image of an institution. The use of a public relations strategy was applied by the public relations officer of Sawah Besar District to help build the image of the DKI Jakarta government through the DKI Jakarta government's work program, namely social assistance for the community, especially in the Sawah Besar District area. The purpose of the study was to determine the Public Relations Strategy in Building the Image of the DKI Jakarta Government. This type of qualitative research with a descriptive approach and constructivist paradigm. Data obtained by using interviews and observations, analyzed with aspects of public relations strategy. The results of this study indicate that the Public Relations of Sawah Besar District uses operational strategies and persuasive and educative approaches to approach the community so that they can build public views on the image of the DKI Jakarta government.